2020
DOI: 10.3390/healthcare8020149
|View full text |Cite
|
Sign up to set email alerts
|

Compression Stocking Length Effects on Oedema, Pain, and Satisfaction in Nursing Students: A Pilot Randomized Trial

Abstract: Professional practitioners who are required to stand for long periods of time frequently complain about vein-related symptoms. Compression stocking are effective for vein-related symptoms, but there is not enough evidence on the effect of the length of compression stockings for nursing students. To compare oedema, pain, and satisfaction according to different lengths of compression stockings worn by female nursing students. This study was conducted as a randomized clinical trial. The participants included 20 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…For the length of compression stockings, more nurses in the current study wear knee-length compression stockings, and there was no difference in symptom relief. This result was similar to the study of Lee et al, 27 that compared edema, pain, and satisfaction according to different lengths of compression stockings worn by female nursing students; no differences were found, but side effects appeared in participants wearing the thigh-length stockings. Besides, knee-length compression stockings were reported to be more comfortable, encouraging higher levels of adherence.…”
Section: Discussionsupporting
confidence: 91%
“…For the length of compression stockings, more nurses in the current study wear knee-length compression stockings, and there was no difference in symptom relief. This result was similar to the study of Lee et al, 27 that compared edema, pain, and satisfaction according to different lengths of compression stockings worn by female nursing students; no differences were found, but side effects appeared in participants wearing the thigh-length stockings. Besides, knee-length compression stockings were reported to be more comfortable, encouraging higher levels of adherence.…”
Section: Discussionsupporting
confidence: 91%
“…7 Up to our knowledge, no data are available to significantly demonstrate the preference of below or above knee GCS. 24 The VFI values assessed in Group B patients confirmed the venous hemodynamic role of GCS: an effect to be added to edema control, and the VVSymQ and CIVIQ quality of life scores improvement. This latte aspect was of great importance considering the known impact of CVD on quality of life.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, wearing a stocking of 18-29 mmHg pressure at the ankle and 15-23 mmHg at the calf reduced edema in the lower limb and enhanced quality of life [9]. The products applying 25-32 mmHg at the ankle, 18-22 mmHg at the calf, and 10-13 mmHg at the thigh were all shown to have positive effects on reducing edema and pain [10]. The findings collectively indicated that compression products with an optimum level of clothing pressure based on the characteristics of the user had positive effects on blood flow.…”
Section: Introductionmentioning
confidence: 99%